(untitled) (PerCursos, 2024)
Defined by a history of slavery, Brazilian society still bears the remnants of this system, nurturing the racist thinking that continues to permeate social, historical, and political spheres, resulting in a social structure built upon discriminatory and violent actions. Consequently, the Black body becomes a target of necropolitics, where living in contemporary times entails experiencing the realities of fear and pain – even at the hands of public institutions meant to protect them. In Brazilian literature, this legacy has been present since its beginnings, manifesting in the marginalization of Black characters. This manifested itself through the normalization of negative stereotypes. Additionally, Black characters were often assigned secondary roles, relegating them to complete silence. In this perspective, by analyzing Jeferson Tenório’s work, O avesso da pele (2020), we aim to illustrate how the author portrays these Black bodies in contemporary Brazilian society, not only in terms of how they are (not) seen but also through their depths and resistance. The theoretical framework draws upon scholars such as Achille Mbembe (2018), Abdias do Nascimento (2016), Chimamanda Adichie (2019), Silvio Luiz de Almeida (2019), Célia Azevedo (1987), Luiz Cuti (2010), Lilia Schwarcz (2013), and Neusa Souza (1983). We can conclude that when the Black body itself appropriates the literary voice, fully aware of its position and immersed in the political and social fabric that surrounds it, it can break free from the chains of racist paradigms, weaving stories that enable the (re)telling and (re)presentation of their own realities to the world.